Measuring and monitoring biodiversity in tropical and temperate forests: proceedings of a IUFRO symposium held at Chiang Mai, Thailand August 27th-September 2nd 1994 - Boyle, T.J.B.; Boontawee, B. (Center for International Forestry Research, 1995)
Many estimates suggest that the world’s forests are home to more than 50% of terrestrial biodiversity, yet temperate and tropical forests face numerous threats, including agricultural and industrial expansion, climate change, non-sustainable management and pollution. If forests and their diversity of living organisms are to be conserved, there is a need to measure and monitor biodiversity, in order that the impact of human activities and the efficacy of conservation measures can be assessed. As the concept of biodiversity covers the range of life itself, from genes to ecosystems, measurement and monitoring is extremely complicated.